Analytical Study of Gastric Tube Vascularization - Gastambide, Carmelo M; Aliano, Franklin (Cirugía del Uruguay, 1980)
This analytical study of the stomach iri' general and gastric tubes in particular, comprised 26 anatomic preparations by means of coloured elastomeric material, corrosion by hydrochloric a cid, macro and microscopic disection and angiographies.